Drug‐Drug Interactions With the Hepatitis B Virus Capsid Assembly Modulator JNJ‐56136379 (Bersacapavir). Issue 12 (5th September 2022) - Vandenbossche, Joris; Yogaratnam, Jeysen; Hillewaert, Vera; Rasschaert, Freya; Talloen, Willem; Biewenga, Jeike; Snoeys, Jan; Kakuda, Thomas N.; Palmer, Martyn; Nangosyah, Julius; Biermer, Michael
Abstract: The capsid assembly modulator JNJ‐56136379 (bersacapavir) disrupts hepatitis B virus replication. It is metabolized via cytochrome P450 (CYP) 3A, but little is known about the drug‐drug interactions of JNJ‐56136379 when combined with drugs that inhibit or are metabolized by CYP3A. In a phase 1, open‐label trial (NCT03945539), healthy adults received 1 dose of JNJ‐56136379 with and without 21 days of prior exposure to itraconazole 200 mg (CYP3A inhibitor). In a second phase 1, open‐label trial (NCT03111511), healthy women received 1 dose of drospirenone/ethinyl estradiol and midazolam before and after 15 days of JNJ‐56136379. Itraconazole increased the area under the plasma concentration–time curve (AUC) of JNJ‐56136379 by 38%. JNJ‐56136379 reduced the maximum observed concentration and AUC of midazolam (CYP3A substrate) by 42%–54%, increased AUC of ethinyl estradiol by 1.6‐fold, but had no effect on drospirenone pharmacokinetics. Overall, these results demonstrated that a strong CYP3A inhibitor (itraconazole) modestly increased JNJ‐56136379 exposure. Furthermore, JNJ‐56136379 was a weak inducer of CYP3A (midazolam) and increased ethinyl estradiol exposure; coadministration of high‐dose estrogen‐based contraceptives and JNJ‐56136379 is not recommended.